Therapeutic Effectiveness and Safety of Mesotherapy in Patients with Osteoarthritis of the Knee. (4th January 2018) - Chen, Liang; Li, Dongqing; Zhong, Jun; Qiu, Bo; Wu, Xianglei
Abstract : Objective . To evaluate the therapeutic effectiveness and safety of mesotherapy by comparing it with the classic systematic therapy in patients with osteoarthritis (OA). Methods . Sixty patients were included and classified into two groups based on the existence of contraindications for nonsteroidal anti-inflammatory drugs (NSAIDs). These patients were treated with oral NSAIDs (Group A) or mesotherapy (Group B). After completing the treatment, the patients were followed up for 6 months. Their clinical features, laboratory results, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were evaluated. Results . A total of 50 patients completed treatment and follow-up. The patients in Group B had significantly fewer gastric acid-related complaints and requested less supplementary treatment for recurrent pain ( p < 0.05 ) . The patients in both groups exhibited decreased blood viscosity after treatment ( p < 0.05 ) . WOMAC scores, specifically those for pain and stiffness, were found to be significantly improved after either type of treatment ( p < 0.05 ) . Mesotherapy also ameliorated physical function ( p < 0.05 ) . Furthermore, Group B presented with better outcomes than Group A (p < 0.05 or p < 0.01 ). Conclusion . Our results suggest that mesotherapy is an effective and safe treatment for patients with OA. Clinicians should consider mesotherapy as an alternative therapy for patients with contraindications for NSAID use.